Transnational planning systems, local practices and spatial inequalities: housing the working classes in Cape Town 1900-970 - Attwell, Melanie Jane (Department of Historical Studies, 2026)
This thesis examines residential planning in Cape Town in the first 70 years of the 20th century, a pivotal period in the creation of residential space for the working classes. It is a contribution to the under-researched history of urban planning in South Africa. This approach means writing history ‘from above' of the spatial and material development of the city rather than a social history ‘from below' of the urban experience in the city, although the two will be intimately connected. Hence, in Henri Lefebvre's conception of the social construction of space, there is a focus on what he referred to as its ‘generative process'. The focus of this thesis is therefore on the ‘generative processes of knowledge, the results of a complex matrix of international influences and local modifications within an ideological context. Little by way of South African urban historiography has explored this unfolding process. It is one that, by using the case study of Cape Town, has attempted to explain both transnational and local influences in a detailed analysis of its material development over more than two-thirds of the 20th century. To this end, I have drawn on a wide range of original sources, including many that have been little drawn on until now, including photographic collections, aerial photographs, historical maps and town plans. I also consulted professional journals and the relevant laws and ordinances. The thesis sheds light on a ‘generative process' in three key areas. The first is to demonstrate the role played by a corps of professional experts in Cape Town in applying international ‘solutions' to the problems confronting the old city. Their working ideas were based on the intellectual public health and planning frameworks in general currency in Britain, Europe and the United States. The ideas had a profound impact on the character, society and form of Cape Town. The second is to show the genealogy of a progression of housing types and residential forms. Their production (with some exceptions) arose from housing forms influenced by transnational and local planning influences and housing models. The third is to highlight the ways in which the planning of working-class housing, even before the apartheid era, contributed towards the growth of residential racial segregation. The trend towards residential segregation was enforced through policy, practice and law and differed from one South African city to another. The growth of residential segregation was accompanied by the centralisation of administrative control, to the extent that racial criteria eventually played the central role in all aspects of residential development and town planning, resulting in the unequal development of physical space along racial lines. The legacy of this ‘generative process' is still clearly apparent in contemporary Cape Town more than three decades after the repeal of apartheid legislation.